A Systematic Literature Review of Contingency Theory in Management Accounting and Control Systems (2010–2024) - Norman Silalahi; Sambas Ade Kesuma (IKRAITH-EKONOMIKA, 2025)
Contingency theory is one of the conceptual frameworks that is widely used in management accounting research and management control systems. This theory assumes that the effectiveness of accounting and control systems cannot be universally determined, but rather is influenced by the compatibility between organizational characteristics and the contextual factors that surround them. Although this theory has been a major reference in various empirical studies, there has not been a systematic review that comprehensively maps how contingency theory is applied, developed, and integrated with other theories in the context of modern management accounting. This study aims to conduct a systematic literature review (SLR) of studies that apply contingency theory in the field of management accounting and management control systems during the period 2010 to 2024. This study uses an approach that refers to the guidelines of Kitchenham and Charters (2007), with the stages of planning, implementation, and reporting which include automatic and manual literature search, application of inclusion-exclusion criteria, quality assessment, and data extraction process. The results of the review show that most studies combine contingency theory with other theories such as Institutional Theory, Resource-Based View, and Agency Theory to strengthen the conceptual foundation. The most frequently studied contextual variables include environmental uncertainty, organizational strategy, company size, and technology support. In addition, the quantitative approach with Structural Equation Modeling (SEM) or Partial Least Squares (PLS) survey and analysis methods dominated the studies studied. Theoretically, this study contributes by presenting a comprehensive picture of the development and direction of research based on contingency theory. The results of this study are expected to be the basis for the development of a conceptual model that is more adaptive to organizational dynamics and an increasingly complex business environment. Keywords: contingency theory, management accounting system, management control system, systematic literature review, management accounting.